2022
DOI: 10.1186/s12885-022-10120-6
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating levels of PCSK9, ANGPTL3 and Lp(a) in stage III breast cancers

Abstract: Background / synopsis Cholesterol and lipids play an important role in sustaining tumor growth and metastasis in a large variety of cancers. ANGPTL3 and PCSK9 modify circulating cholesterol levels, thus availability of lipids to peripheral cells. Little is known on the role, if any, of circulating lipid-related factors such as PCSK9, ANGPTL3 and lipoprotein (a) in cancers. Objective/purpose To compare circulating levels of PCSK9, ANGPTL3, and Lp(a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Indeed, only one recent study on a small sample size (n = 46) of women with stage III breast cancer has been conducted, reporting increasing levels of PCSK9 with the severity of breast disease. However, no prognostic conclusions were made [14]. A pancancer analysis found that PCSK9 expression was considerably higher in invasive breast We also evaluated the influence of other risk biomarkers, both as confounders and risk stratifiers, and different cut-off points for PCSK9, but the results did not change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, only one recent study on a small sample size (n = 46) of women with stage III breast cancer has been conducted, reporting increasing levels of PCSK9 with the severity of breast disease. However, no prognostic conclusions were made [14]. A pancancer analysis found that PCSK9 expression was considerably higher in invasive breast We also evaluated the influence of other risk biomarkers, both as confounders and risk stratifiers, and different cut-off points for PCSK9, but the results did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only one recent study on a small sample size (n = 46) of women with stage III breast cancer has been conducted, reporting increasing levels of PCSK9 with the severity of breast disease. However, no prognostic conclusions were made [14]. A pan-cancer analysis found that PCSK9 expression was considerably higher in invasive breast carcinoma [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 331 This observation is in harmony with a recent clinical study involving 46 cases, which suggested that PCSK9 levels could escalate in proportion to the severity of breast disease, with the lowest levels found in benign disorders while the highest in stage III breast cancer. 333 Such evidence accentuates the potential utility of PCSK9 as a diagnostic and prognostic biomarker in breast cancer.…”
Section: The Role Of Pcsk9 In Various Disordersmentioning
confidence: 99%
“…Patients with liver cirrhosis exhibit lower serum PCSK9 levels, while these levels are increased in patients with hepatitis C virus (HCV)-induced liver cirrhosis ( 52 ). PCSK9 levels increase with the severity of breast cancer ( 53 ). These specific pathological conditions may lead to changes in thrombosis or haemostasis.…”
Section: Pleiotropic Effects Of Pcsk9 On Cardiovascular Diseasementioning
confidence: 99%